Efektifitas dan Kontribusi Penagihan Pajak dengan Surat Paksa dan Surat Teguran dalam Meningkatkan Penerimaan Pajak Pada Kantor Pelayanan Pajak Pratama Makassar Barat. - Payu, Anita Achmad; Marlinah, Andi (Restitusi : Jurnal Riset Perpajakan, 2023)
The Focus of this research examines how the effectiveness and contribution of tax collection with forced letters and warning letters in increasing tax revenue at the north makasar KPP Pratama Office. Purpose study see effectiveness of tax revenue based on billing with forced letters and warning letters. Study also uses secondary data, namely tax revenue redporting from 2016 until 2018, with a descriptive analysis method using an effectiveness ratio. Result study from West makassar. Minimizes the issuance of forced letters sending SKP (tax assessment letters) and STP (tax Collection letters) to taxpayers (WP) who have tax arrears over 100 million. And then two leterrs will later sent to collection of west makassar paratama tax office, via posr delivery to the taxpayer’s address.